Exploring the barriers to cervical screening and perspectives on new self-sampling methods amongst under-served groups - Stephanie Gillibrand; Helen Gibson; Kelly Howells; Sean Urwin; Jennifer C. Davies; Emma J. Crosbie; Caroline Sanders (BMC Health Services Research)
Abstract Background Cervical screening rates have fallen in recent years in the UK, representing a health inequity for some under-served groups. Self-sampling alternatives to cervical screening may be useful where certain barriers prohibit access to routine cervical screening. However, there is limited evidence on whether self-sampling methods address known barriers to cervical screening and subsequently increase uptake amongst under-screened groups. Addressing this research gap, the study aims to understand experiences during and barriers to attending cervical screening for under-screened groups and; explore the views of individuals eligible for screening towards self-sampling (vaginal swabbing and urine sampling) as alternative screening methods and how this may address existing barriers to screening. Methods We draw on three integrated theoretical frameworks (access to primary care services, intersectional and feminist perspectives) to examine participants’ barriers to screening and views toward self-sampling methods. We undertook primary qualitative data collection (interviews and focus groups) with 46 participants, facilitated by collaborations with the VCSE sector which successfully enhanced reach to under-served communities. Results Known barriers to cervical screening persist for under-screened participant groups, but we also find numerous examples of good practice where some participants’ needs were met throughout the screening process. Both positive and negative experiences tend to centre around experiences with healthcare professionals, with negative experiences also centring around the use of the speculum. Self-sampling methods (vaginal swab and urine collection) were positively received by participants, and may address some existing barriers through the proponents of enhanced choice – between method and location (which also dovetailed with convenience) leading to greater empowerment. The removal of the speculum and lack of invasive examination by a healthcare professional was also positively received. Conclusions Whilst barriers to cervical screening remain for under-served groups, examples of good practice are prevalent. Such examples should be implemented more widely to ensure consistency in patient experience and to ensure needs are better met for under-served groups. The introduction of self-sampling alongside traditional methods may reduce barriers to screening, and may boost screening rates for under-screened groups but only if they are implemented with appropriate information and sufficient communication. Failure to implement self-sampling without these considerations may threaten to undermine the identified and important benefits of self-sampling methods.